PENGARUH DIAMETER DAN BAHAN RESONATOR KNALPOT TERHADAP EMISI GAS BUANG DAN TINGKAT KEBISINGAN MESIN 1000 CC: ANALYSIS OF THE EFFECT OF EXHAUST RESONATOR DIAMETER AND MATERIAL ON EXHAUST EMISSIONS AND NOISE LEVEL OF 1000 CC ENGINE - Berlyanto Dwi Arrokhman; Ratna Monasari (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
This study aims to determine the effect of different diameter sizes and materials used in the manufacture of exhaust resonators on vehicle engines, especially in four-wheeled vehicles or gasoline-fueled cars. This research uses experimental research methods, namely by comparing the use of resonators made of galvanized steel and stainless steel with different diameter sizes of 100 mm and 125 mm, the research object used is a Suzuki Jimny LJ80V car with a 1000 cc engine. The data taken are the results of exhaust emissions testing and noise testing of galvanized steel resonators with diameters of 100 mm and 125 mm and stainless steel resonators with diameters of 100 and 125 mm. Based on the results of the noise test, the 125 mm galvanized steel resonator can reduce noise with a result of 94.5 dBA at 6000 rpm. In the exhaust gas emission test, the lowest HC exhaust gas is produced by stainless steel resonator at 198.3 ppm at 3500 rpm, the lowest exhaust gas by 100 mm galvanized steel resonator at 0.15% at 1000 rpm.